2014
DOI: 10.1038/srep06065
|View full text |Cite|
|
Sign up to set email alerts
|

Laser spectrometry for multi-elemental imaging of biological tissues

Abstract: An increasing interest has arisen in research focused on metallic and organic ions that play crucial roles in both physiological and pathological metabolic processes. Current methods for the observation of trace elements in biological tissues at microscopic spatial resolution often require equipment with high complexity. We demonstrate a novel approach with an all-optical design and multi-elemental scanning imaging, which is unique among methods of elemental detection because of its full compatibility with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 46 publications
1
84
0
4
Order By: Relevance
“…The instrument used to provide the LIBS images has been described in [12] and [13] (laser source was a Nd:YAG emitting 8 ns pulses at 1064 nm with a 100 Hz repetition rate; laser energy was reduced at typically 1.5 mJ; laser pulses were focused onto the sample by a 15× magnification objective resulting in a crater size close to 8 µm). The spatial distributions of Mg and Sr were found to be rather similar in the external layer (Figure 8a and 8c).…”
Section: Photonic Methods and Resultsmentioning
confidence: 99%
“…The instrument used to provide the LIBS images has been described in [12] and [13] (laser source was a Nd:YAG emitting 8 ns pulses at 1064 nm with a 100 Hz repetition rate; laser energy was reduced at typically 1.5 mJ; laser pulses were focused onto the sample by a 15× magnification objective resulting in a crater size close to 8 µm). The spatial distributions of Mg and Sr were found to be rather similar in the external layer (Figure 8a and 8c).…”
Section: Photonic Methods and Resultsmentioning
confidence: 99%
“…LIBS imaging, a novel advanced technique to specifically detect heavy metals/elements showed heterogeneous distribution of gold (RGD:AuNP) in the tumor tissue. 55,56 The spectral read-outs resonated with corresponding peaks for gold in the treated samples vs nontreated samples ( Figure 3I Other reported studies have shown that ≈10 nm-sized gold nanoparticles that accumulate in the liver (kupffer cells) are eventually cleared by the hepatobiliary pathways. 57 In addition to this, the collimated radiation setup that we employed largely reduces RGD:AuNP activation in off-target organs such as the liver.…”
mentioning
confidence: 80%
“…The imaging capability of Laser-induced breakdown spectroscopy (LIBS) represents an attractive way of development for the technique, with innumerable applications in various fields, such as geology [1][2][3], industry [4][5][6][7][8], surface science [9,10] and biology [11][12][13][14][15]. In LIBS imaging, laser-induced plasma are generated continuously while scanning the sample surface over the region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has many advantages such as multielemental capability, ease in use, and operation at atmospheric pressure. This is furthermore the only all-optical technique providing space-resolved elemental information with a ppm-scale sensitivity and a µm-range resolution [12]. Another asset of the technique lies in its acquisition speed.…”
Section: Introductionmentioning
confidence: 99%